Effects of praziquantel on common carp embryos and larvae - Velisek, Josef; Zuskova, Eliska; Kubec, Jan; Sandova, Marie; Stara, Alzbeta (Scientific reports, 2022)
This study aimed to assess the toxicity of praziquantel (anthelmintic drug) in different developmental stages of common carp (Cyprinus carpio) based on mortality, early ontogeny, growth, oxidative stress, antioxidant enzymes, histology and behaviour. Praziquantel at all tested concentrations ranging from 1 to 4 mg/L showed no significant adverse effects on mortality, the early ontogeny and behaviour locomotory (activity, moved distance and velocity) of carp after 35-day exposure. Concentrations of 3 and 4 mg/L caused significantly (P < 0.01) lower growth, total superoxide dismutase and catalase activities compared with controls. Praziquantel is safe for the early life of carp in concentrations ≤ 2 mg/L.
Keywords: Praziquantel; Water Pollutants, Chemical; embryo nesavčí; Carps; Larva; antioxidancia; katalasa; Superoxide Dismutase; Animals; praziquantel; superoxiddismutasa; Embryo, Nonmammalian; Antioxidants; zvířata; kapři; chemické látky znečišťující vodu; Catalase; larva